Facts and prospects of peptide in targeted therapy and immune regulation against triple-negative breast cancer - Huang, Yongxiu; Zeng, Anqi; Song, Linjiang (Frontiers in Immunology, 2023)
Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer. Due to the lack of specific therapeutic targets, treatment options are limited, and the recurrence and metastasis rate is high, the overall survival of patients is poor. However, with the discovery of some new targets and the corresponding immune regulation after targeting these targets, TNBC has a new hope in treatment. The peptide has a simple structure, strong binding affinity, and high stability, and has great potential in targeted therapy and immune regulation against TNBC. This review will discuss how single peptides and peptide combinations target triple-negative breast cancer to exert immunomodulatory effects. Among them, single peptides target specific receptors on TNBC cells, act as decoys to target key ligands in the regulatory pathway, and target TME-related cells. The combinations of peptides work in the form of cancer vaccines, engineered exosomes, microRNAs and other immune-related molecular pathways, immune checkpoint inhibitors, chimeric antigen receptor T cells, and drug-peptide conjugates. This article is mainly dedicated to exploring new treatment methods for TNBC to improve the curative effect and prolong the survival time of patients.